2018
DOI: 10.1002/celc.201700970
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur‐Containing Molecules Grafted on Carbon Nanotubes as Highly Cyclable Cathodes for Lithium/Organic Batteries

Abstract: Lithium/organic and lithium/sulfur batteries have attracted great interest lately due to their high theoretical specific capacity and potential low cost. However, two major roadblocks currently prevent industrial development of these kind of batteries: (i) the progressive dissolution of active material in the electrolyte which hinders cyclability of the devices and; (ii) the electrical insulating nature of organic or sulfur materials. In this work, we show an elegant solution to solve both, the conductivity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The covalently functionalized system presents 95% of the initial capacity after 50 cycles. 144 By grafting anthraquinone diazonium salts to MWCNTs (MWCNTs-AQ), 98% of the initial capacity was retained after 50 cycles. 145 Besides covalent functionalization, the structure of redox-active molecules also plays a great role in the stability of the electrodes.…”
Section: Covalent Functionalization Ofmentioning
confidence: 99%
“…The covalently functionalized system presents 95% of the initial capacity after 50 cycles. 144 By grafting anthraquinone diazonium salts to MWCNTs (MWCNTs-AQ), 98% of the initial capacity was retained after 50 cycles. 145 Besides covalent functionalization, the structure of redox-active molecules also plays a great role in the stability of the electrodes.…”
Section: Covalent Functionalization Ofmentioning
confidence: 99%
“…[15,16] To solve these current issues, many pioneering strategies have been developed to confine soluble polysulfide species and alleviate their diffusion in recent years. The most popular strategy is to prepare appropriate sulfur host materials, such as porous carbon matrix, [17][18][19] carbon nanotubes/ fibers, [20,21] metal-organic frameworks, [22][23][24][25] and covalent organic frameworks. [26,27] Meanwhile, transition metal sulfides, [28,29] metal oxides, [30] and metal nitrides [31,32] have been generally prepared to modify those host materials.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, unexpectedly weak reduction processes and negligible electron mobility were observed depriving the desired study of the resulting copolymer. Our attention then turned to nanotube dispersion as recent reports have demonstrated that interactions between redox organic molecules and carbon nanotubes can increase the conductivity of the organic materials. ,, It can also facilitate redox reactions by π–π interactions with the nanotubes in addition to overcoming the inherent dissolution problem. In this study, single-walled carbon nanotubes (SWCNTs) were dispersed with the copolymer using the conjugated polymer-assisted dispersion method . High concentration dispersion was filtered to obtain a freestanding film that was used directly as a cathode.…”
Section: Introductionmentioning
confidence: 99%